Analisis Kontribusi Pemanfaatan Limbah Kantong Semen (Reject) Berdasarkan Prespektif Life Cycle Assessment (Studi Kasus : PT. Solusi Bangun Indonesia Tbk.) - Harjanto, Taufan Ratri; Prastya, Andika; Bahri, Saipul; Prasadi, Oto (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2023)
PT. Solusi Bangun Indonesia (SBI) Tbk Cilacap Factory is a cement company in Cilacap that has a high commitment and awareness of resource efficiency and the use of renewable energy. One of the important things that can support resource efficiency programs is the management of non-hazardous (non-B3) solid waste. If managed properly, non-B3 solid waste can produce a circular economy that is beneficial for the company and the community. PT SBI Cilacap Factory is making efforts to develop a Circular Economy with an LCA approach to cement bags produced both as reject products and circulating to end users through community empowerment activities. This study aims to evaluate the comprehensive environmental impact of the reduce, reuse, recycle, and recover cement bag program conducted by PT SBI Cilacap Factory together with the community. The system based on the purpose of this study cannot use a cradle-to-grave. Data processing in this study for environmental impact evaluation used the LCA SimaPro-9.4.0.2 software. The impact assessment method uses the ReCiPe 2016 midpoint method. Based on the contribution analysis, it was found that the cement paper collected for recycling in a centralized recycling facility will make a greater contribution to the environmental impacts of terrestrial ecotoxicity, land use, global warming, human non-carcinogenic toxicity, and human carcinogenic toxicity.